Access to and Use of Agricultural Information for Smallholder Farmers ' Adaptation to Climate Change in Iringa Rural District, Tanzania - Sawe, Jackson Raymond (University of Dar es Salaam Library Journal, 2022)
This paper assesses how access to and use of agricultural information contributes to adaptation by smallholder farmers to climate change in Iringa Rural District, Tanzania. Specific objectives of this study were to examine types and sources of agricultural information, to explore the use of agricultural information in climate change adaptation, and to delineate factors affecting farmers ' access to and use of agricultural information for climate change adaptation. The study used a mixed research approach and a sample of 87 heads of household was studied. In-depth interviews, focus group discussions, household survey and field observation were used to collect data. SPSS software was used to analyse quantitative data while content analysis was used to analyse qualitative data. The study has revealed that mass media is the most source of agricultural information used by smallholder farmers, followed by person-to-person interactions between farmers. These sources provide agricultural information that covers proper farming practices, the use of affordable farm implements, soil conservation methods, and use of improved seed varieties. Furthermore, the findings have revealed that a language barrier, unfavourably scheduled radio and television programmes, and insufficient budget to agricultural extension officers are factors affecting farmers ' use of agricultural information. Therefore, smallholder farmers ' ability to respond to climate change is largely dependent on access to and use of agricultural information. Consequent to the findings, it is being recommended that collective efforts between the government and other stakeholders to ensure smallholder farmers ' access to and use of agricultural information for climate change adaptation should be strengthened.